In the land of youth - Stephens, James (Macmillan Co., 1924)
Mythical tales of Ireland.
Half-title: Táin bó cúalgne, In the land of youth.
Mythical tales of Ireland.
Keywords: Celts / Religion. / fast / http://id.worldcat.org/fast/850424; Authors, Irish. / fast / http://id.worldcat.org/fast/822116; Authors, Irish. / http://id.loc.gov/authorities/subjects/sh85009928; Celts / Religion / Fiction.; Fiction. / lcgft / http://id.loc.gov/authorities/genreForms/gf2014026339; Fiction. / fast / http://id.worldcat.org/fast/1423787